Chemical Analysis of Acacia Ehrenbergiana (Salam) Tree Fruits (Seed and Pods) As Dry Season Supplement For Livestock in Arid and Semi –Arid Lands of Sudan - Abdalla, Mohamed S.A; Babiker, Izeldin A; Elkalifa, Kamal F (Animal Review, 2015)
In developing countries farming and livestock keeping are the most dominant activities for the indigenous people, proper farming maintain good and adequate grazing for livestock and hence support livelihood in such countries. Therefore, local inhabitants largely depend on some tree species suitable for grazing purposes. In the present study, the nutritional value for fruits of Acacia ehrenbergiana (Salam) (seeds and pods) at the lower Atbra river basin in north eastern part of Sudan was investigated. Field samples of fruits were collected, each sample kept separately in a small cloth kit. Chemical analysis of fruit samples was conducted to quantify the content of various nutritional attributes including: the crude protein, crude fibers, fats, starch, ash, and moisture content. In addition to some minerals namely P, Ca, Mg, Na, Cur and Fe. Chemical analysis revealed that CP is found to be as high as 30.99%, CF reached 25.11%, the starch content 12.12%, fat 4.1%, and ash content 11.81% .These values showed the high nutritional values fruits. Similarly mineral contents demonstrate good amounts of Na and Ca that needed by livestock for adequate growth, but lower amounts of P that should be supplemented to the diets. Most tested browse fruits revealed adequate nutritional values of Acacia ehrenbergiana (Salam) fruits as a protein or dry season supplement. Fodder trees still need to be fully evaluated in order to reduce the cost of feed . This can be done by being used as a feed supplement to livestock .Increasing the base for feed options (forages) with high quality feed will support the ever increasing demand for livestock products ,as feed is the most important factor influencing livestock production in the harsh environment of the dry lands.